2009
DOI: 10.2134/agronj2009.0108
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Certified and Farm‐Saved Seed on Yield and Quality Characteristics of Canola

Abstract: Relatively high seed prices and low canola (Brassica napus L.) grain prices created a controversy over using farm-saved seed from hybrids. Agronomic implications of saving seed from a canola crop were investigated by planting certifi ed seed and saved-seed of an open-pollinated and a hybrid canola cultivar at eight site-years in Saskatchewan and Alberta, Canada. In one series of experiments cultivars and seed rates were compared, while in another experiment seed treatments and use of sized seed were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
18
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 13 publications
(20 reference statements)
3
18
0
Order By: Relevance
“…With canola grown as a crop in competition with oat, the G2 generation of a hybrid canola variety had a lower yield than the G1 generation (Clayton et al 2009). However, the OP canola variety did not differ in yield between G2 and G1.…”
Section: Mature B Napus Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…With canola grown as a crop in competition with oat, the G2 generation of a hybrid canola variety had a lower yield than the G1 generation (Clayton et al 2009). However, the OP canola variety did not differ in yield between G2 and G1.…”
Section: Mature B Napus Densitymentioning
confidence: 99%
“…Hybrid canola varieties are better than open-pollinated varieties at suppressing weed growth (Zand and Beckie 2002;Harker et al 2003). Furthermore, subsequent generations of hybrids have been observed to have lower yields than the F 1 generation when grown with weeds (Clayton et al 2009). Successive generations of hybrid varieties lose their heterozygosity, and move towards a homozygous state (Hill et al 1998).…”
mentioning
confidence: 99%
“…Trials in Germany reported HYC and HY‐FSS canola yielded higher than the parent lines and HY‐FSS yielded 8.7% less than HYC (Grosse et al, 1992). Similarly, Clayton et al (2009) reported a 12% yield advantage of HYC over HY‐FSS. The yield advantage of HYC over HY‐FSS needs to cover the higher seed cost of HYC seed for HYC to be more profitable.…”
mentioning
confidence: 90%
“…The cost of OPC and HYC seed is higher than FSS, but there are yield, quality, and seed treatment benefits from using certified canola seed (Clayton et al, 2009). The NR benefits of certified seed will be determined by the yield advantage of certified seed, price of the crop, and the cost of seed.…”
mentioning
confidence: 99%
See 1 more Smart Citation